Injury prevention and physiotherapy procedures for ankle injuries in ballet dancers: A literature review - Vilar, Pia Lina; Kovačič, Tine; Gerževič, Mitja (Annales Kinesiologiae, 2023)
The aim of this study was to investigate the most frequent, effective and up-to-date injury prevention and physiotherapy procedures used in relation to ballet dancers’ ankle injuries. A literature review with a qualitative analysis was performed using the following databases: PubMed, SAGE, ScienceDirect, PlosOne and Cochrane Library. The inclusion criteria were: both genders, age > 18, journal impact factor > 0, age of study ≤ 10 years and the following search keywords were used: “ankle”, “injury”, “ballet”, “dancers”, “physiotherapy”, “physical therapy” and “prevention”. A total of 520 articles were found, out of which six were determined to be appropriate according to the inclusion and exclusion criteria. They dealt with the prevention/rehabilitation of ankle sprains (N=2), tendinopathy of the Achilles tendon (N=2), tendinitis of the m. hallucis longus (N=4), rupture of the Achilles tendon (N=2), and anterior (N=3) and posterior (N=4) impingement syndrome. It was found that for injury prevention in ballet, strengthening and stretching exercises are the most often used methods, while rest, ice therapy, muscle strengthening exercises, foot braces and dance technique optimisation are the most frequently used methods in injury management. These seem to also be the most up-to-date injury prevention and physiotherapy procedures, while the most effective procedures could not be retrieved due to a lack of relevant studies, which prevented the quantitative comparison of their effectiveness. The published clinical evidence endorses physiotherapy/kinesiotherapy as an effective ankle injury prevention and management modality in ballet dancers, although additional studies with a better quality of methodology are required.